Two Shi‘i Jurisprudential Methodologies to Address Medical and Bioethical Challenges: Traditional Ijtihād and Foundational Ijtihād - Mavani, Hamid (Journal of religious ethics, 2014)
The legal-ethical dynamism in Islamic law which allows it to respond to the challenges of modernity is said to reside in the institution of ijtihād (independent legal thinking and hermeneutics). However, jurists like Mohsen Kadivar and Ayatollah Faḍlalla have argued that the “traditional ijtihād” paradigm has reached its limits of flexibility as it allows for only minor adaptations and lacks a rigorous methodology because of its reliance on vague and highly subjective juridical devices such as public welfare (maṣlaḥa), imperative necessity (ḍarūra), emergency (iḍtirār), need (ḥāja), averting difficulty (‘usr) and distress (ḥaraj), hardship (mashaqqa), and harm (ḍarar) without interrogating the fundamentals (uṣūl) of ijtihād. In contrast, in the “foundational ijtihād” model theology, ethics, intellect, epistemology, linguistics, hermeneutics, modern sciences, history, cosmology, anthropology, and the sources of Islamic legal theory (uṣūl al-fiqh) interact with one another to obtain resolutions that are just and non-discriminatory.